2019
DOI: 10.1016/j.numecd.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Statins and risk of thromboembolism: A meta-regression to disentangle the efficacy-to-effectiveness gap using observational and trial evidence

Abstract: Background and aims Meta-analyses of randomised controlled trials (RCTs) and observational studies indicate a lower risk of venous thromboembolism (VTE) associated with statin treatment. We aimed to compare the effect of statin therapy in these two settings and to identify and quantify potential factors to explain statin efficacy and effectiveness. Methods and Results We electronically searched on December 11 th , 2018, articles reporting on first VTE events in RCTs (statin vs placebo) and in observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Although an association between statin use and reduced incidence of venous thromboembolism has been described in recent years, we did not collect data on statin use and could not therefore control for it. 19,20 Bone marrow biopsy specimens for patients who progressed to MF were not accessed or systematically reviewed by an independent hematopathologist. We also acknowledge the significant range of disease durations before institutional contact present in our sample, which may present unknown biases related to patient treatment history that are not fully accounted for in our multivariable analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although an association between statin use and reduced incidence of venous thromboembolism has been described in recent years, we did not collect data on statin use and could not therefore control for it. 19,20 Bone marrow biopsy specimens for patients who progressed to MF were not accessed or systematically reviewed by an independent hematopathologist. We also acknowledge the significant range of disease durations before institutional contact present in our sample, which may present unknown biases related to patient treatment history that are not fully accounted for in our multivariable analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Cohort studies 25 suggest statin exposure may reduce VTE risk by 25%, whereas RCTs indicate a 15% reduction in risk 25 and accentuation by intensity of therapy. 25 , 26 , 43 , 44 Differences between cohort and RCT findings may be attributable to differences in patient populations, 45 as well as duration of statin exposure. Statin effectiveness studies typically have a longer median statin exposure time (approximately 4 years) 25 than in this study, where VTE reduction was observed with 90 or more days.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies suggest statin exposure may reduce VTE risk by 25%, 25 while RCTs indicate a 15% reduction in risk 25 and accentuation by intensity of therapy. 25,26,43,44 Differences between cohort and RCT findings may be attributable to differences in patient populations, 45 as well as duration of statin exposure. Statin effectiveness studies typically have a longer median statin exposure time (approximately four years) 25 than in this study, where VTE reduction was observed with 90 or more days.…”
Section: Discussionmentioning
confidence: 99%